The judicial reaction against the public utilities changes: using consumer law in telecommunications’ demands in Brazil - Veronese, Alexandre (Direito.UnB - Revista de Direito da Universidade de Brasília, 2019)
The public utilities privatizations, which were carried on many Latin American countries in the nineties, had many political different reactions. In Brazil, it became visible the judicial consumer reaction against the new regulatory model in most public utilities. There were some factors that allowed the judicial system to be flooded with the network industries lawsuits. The hypothesis of the paper is that one of the causes was the absence of a suitable legal and institutional framework to channel the consumer demands. On the other side, some new types of judicial procedures (like class actions, on one side, and special claim courts, otherwise) gave the strength to the Brazilian judicial power to raise as a central player in order to decide and directly determine the legal details of the public utilities production and distribution.